Etika Pelayanan Publik di Kantor Kelurahan Rabangodu Utara Kecamatan Raba Kota Bima - Ari Kamandanu (Journal of Research and Development on Public Policy, 2022)
This study aims to determine the ethics of public services at the North Rabangodu Village Office, Raba District, Bima City. The type of research used is qualitative research. The data sources used are primary and secondary. The number of informants is 6 people. Data collection was carried out using observation, interview and documentation techniques. Data analysis techniques using data reduction steps, data presentation, data verification, and using triangulation data validation, namely triangulation of sources, techniques, and time. The results showed that the public service ethics applied at the North Rabangodu Village Office, Raba Subdistrict, Bima City have not been fully implemented properly when viewed from the aspect of 1) Equality of rights, equality of rights has been running well, serving the community regardless of race, ethnicity, religion and politics, 2) Justice, serving the community in a friendly manner, providing explanations during the service process, serving the community, all communities are treated equally, 3) Loyalty, employees, especially honorarium, are still loyal to the agency regardless of how much salary they receive and have even worked for years, 4) Accountability, not yet fully done well.